Comparison of various sire evaluation methods in a herd of Holstein Friesian cattle - ASWATHANARAYANA, T (The Indian Journal of Animal Reproduction, 2003)
Relative efficiency of the sire evaluation procedures based on minimum standard error ofprocedures indicated that both BLUP and MCC methods were more appropriate and efficient inestimating the breeding values of sires compared to SDA and CC. The accuracy and efficiency ofBLUP and MCC procedures was probably due to their ability to remove the inherent biases in thedata which are likely to arise from sampling sire progeny, progeny per sire effect of geographicallocation, period and season. In general, BLUP procedure was found to be the best in its applicationdue to its consistency and unbiasedness in ranking of sires in comparison to other procedures. Thepresent findings strongly recommend the use of BLUP procedure for evaluating sires under field andfarm conditions, since the BLUP procedure had an advantage over MCC, especially in the absence ofdata on contemporary daughters.
Keywords: Sire evaluation; reproductive traits; BLUP